Research of Mechanical Resonance Analysis and Suppression Control Method of the Servo Drive System - Wenli Li; Yongkang Liu; Shuaishuai Ge; Daming Liao (Shock and Vibration)
Transmission mechanisms of the servo drive system are not a pure rigid body, and the existence of the elastic transmission mechanisms will make the system generate mechanical resonance. Aiming at mechanical resonance of the servo drive system, the resonance generation mechanism is analyzed, the four-mass model considering the time-varying meshing stiffness of the gear is established, and the influence of different stiffness parameters on the mechanical resonance of the system is researched in this paper. The composite controller of Model Predictive Control (MPC) with Notch Filter is used to simulate the mechanical resonance suppression of the four-mass servo system considering time-varying meshing stiffness, and it is compared with the mechanical resonance suppression method based on Model Predictive Control. The simulation results show that when the step speed is 200 r/min, the overshoot is reduced from 11.6 r/min to 1.1 r/min, which is reduced by 90.5%. Under the impact load condition, from 10 Nm to 30 Nm, overshoot is reduced from 34.3 r/min to 12.8 r/min, reduced by 62%, and torque oscillation is reduced by 81.5%. Therefore, the composite controller of Model Predictive Control with Notch Filter can suppress the mechanical resonance problem effectively, caused by elastic transmission, and improve the robustness of servo drive system.